Corrosion behavior of biodegradable metals in two different simulated physiological solutions: Comparison of Mg, Zn and Fe. (15th April 2021) - Dong, Hongzhou; Lin, Fei; Boccaccini, Aldo R.; Virtanen, Sannakaisa
Highlights: Comparison of Mg/Zn/Fe under the same experimental conditions in two different simulated physiological solutions. Ranking the corrosion rate of Mg/Zn/Fe as a function of immersion time. Identifying the different influence of the composition of the physiological solutions between three metals. Abstract: Bio-absorbable metals have been proposed to overcome the limitations of permanent implant materials, particularly the risk of chronic inflammation and secondary surgery for removal after healing. The most researched bio-absorbable metal is magnesium, followed by iron and zinc, but there is little work comparing the different metals under the same experimental conditions. Herein, degradation performance of Mg/Zn/Fe was investigated via immersion test (28 days) and electrochemical tests under two buffer systems, simulated body fluid solution (SBF) and Dulbecco's Modified Eagle's cell culture medium (DMEM). Corrosion rate was initially slower in DMEM for all metals, Mg showed the fastest corrosion rate in both SBF and DMEM. The influence of the electrolyte on the corrosion behaviour was strongest for Mg. Importantly, the ranking of the corrosion rate of the three metals changes with immersion time. Noteworthy is a strong increase of corrosion resistance of Mg with time during the first 24 h of immersion. Corrosion morphology and corrosion products were characterized with SEM, EDS, FTIR, XPS and XRD. In general, the corrosion product layers are much more uniform in DMEM, besides, the insoluble corrosion product/precipitation consisted of metallic oxides/hydroxides, phosphates and carbonates. Slower corrosion rate in DMEM solution can therefore be due to formation of a more protective precipitate layer, adsorbed amino acids, and absence of Tris-HCl that accelerates corrosion in SBF.